Trial Of Life (Fitnah) From The Stories In Surah Al-Kahf According To Sayyid Qutb In Tafsir Fii Zhilal Al-Qur’an - Ali, Ali Mahfuz; Rifaannudin, Mahmud; Naufal, Aulia; Al-Bari, Fildzah Khoirina (ZAD Al-Mufassirin, 2024)
In Islam, slander is considered more cruel than murder because it can lead a person to lose their beliefs and commit worse acts. Many are unaware of the various forms of slander in their lives, which can be both good and bad. This study aims to reveal the forms of slander in Qur'anic stories according to Sayyid Qutb, a story-patterned mufassir. Using literature research and descriptive analysis, Qutb interprets the story of Asḥābul Kahf as a test of faith through pagan rulers and societies. In Shaḥibul Jannatain, there is a test of wealth, contrasting a proud, wealthy young man with a grateful, less wealthy one. The story of Moses and the Servant of God depicts a test of knowledge, with Moses humbly seeking knowledge. In the story of Dzulkarnain, a test of power is shown, where Dzulkarnain remains grateful and wise despite his unlimited power.